Hypersensitive reaction to tattoos: A growing menace in rural India - B M Shashikumar; M R Harish; B Shwetha; M Kavya; K Deepadarshan; H N Phani (Wolters Kluwer Medknow Publications, 2017)
Background: Increased enthusiasm toward newer fashion trends among rural India along with the lack of government regulation has led to increased tattoo reactions. Objective: The objective of this study is to describe various clinical manifestations of hypersensitive reactions to tattoo ink reported at a tertiary care hospital in Mandya district. Materials and Methods: An observational study was carried out over a period of 1 year from June 2014 to May 2015 at Mandya Institute of Medical Sciences, Mandya. All the patients reporting with allergic reaction due to tattooing were included in the present study after obtaining informed consent. Transient acute inflammatory reaction, infections, and skin diseases localized on tattooed area were excluded from this study. A detailed history regarding the onset, duration and color used for tattooing were collected. Cutaneous examination and biopsy was to done to know the type of reaction. Results: Fifty cutaneous allergic reactions were diagnosed among 39 patients. Mean age of subjects was 22 years and mean duration before the appearance of lesion was 7 months. Common colors associated with reactions were red (53.9%), black (33.3%), green (5.1%), and multicolor (7.7%). Itching was the predominant symptom. Skin lesions mainly consisted of lichenoid papules and plaques, eczematous lesions, and verrucous lesions. Lichenoid histopathology reaction was the most common tissue allergic reaction. Conclusion: Increasing popularity of tattooing among young people has predisposed to parallel increase in adverse reactions. Red pigment is most common cause of allergic reaction in the present study, and lichenoid reaction is the most common reaction.